Estudo da cristalização de niobato de lítio (liNbO3) em vidros niobatos por espectroscopias Raman, infravermelho, Mossbauer e função dielétrica complexa - Almeida, Emerson Ferreira de (1997)
In this work the glass family 0.5Li2O : (0.5-x)P2O5 : xNb2O5 : yFe2O3, with 0 < x < 0.5 (mol %) and y =0, y = 0.02, = 0.05, y = 0.I (mol %) was prepared using the melt quenching technique and studied using infrared spectroscopy, Mbssbauer spectroscopy, Raman Scattering, x-ray diffraction, Complex Dieletric Function and DSC. The use of these techniques gives new informations about the crystallization of Lithium Niobate (LiNbO3) on the samples with high concentration of niobium in this glass family.